Hepatic Arterial Infusion Chemotherapy for Hepatocellular Carcinoma: A Three-Dimensional Visualization Perspective - Tan Y; Li PP; Liu H; Zhu JY; Wu QS (Journal of Hepatocellular Carcinoma)
Yong Tan,1 Ping-Ping Li,2 Hui Liu,1 Jian-Yong Zhu,3 Qing-Song Wu1 1Department of Hepatobiliary Surgery, Yuebei People’s Hospital, Shaoguan, Guangdong, 512026, People’s Republic of China; 2Department of Ophthalmology, Yuebei People’s Hospital, Shaoguan, Guangdong, 512026, People’s Republic of China; 3Department of Hepato-Pancreato-Biliary Surgery, The First Medical Center of PLA General Hospital, Beijing, 100853, People’s Republic of ChinaCorrespondence: Qing-Song Wu, Email 308397082@qq.comAbstract: In Asia, hepatic arterial infusion chemotherapy is an alternative therapeutic option for hepatocellular carcinoma (HCC). However, the current application of HAIC lacks precision, as drug dosages are typically calculated based solely on body surface area. This approach often results in underdosing for patients with larger liver tumors or greater liver volume and overdosing for those with smaller liver tumors or reduced liver volume. Consequently, determining drug dosages according to the specific target volume requiring treatment may enhance individualized and standardized therapy for HCC, aligning with the principles of precision oncology.Keywords: hepatic arterial infusion chemotherapy, hepatocellular carcinoma, target volume, precision